Problem nutrients in diet of under-five children and district food security status: Linear programming analyses of 37 stunting priority districts in Indonesia. - Umi Fahmida; Indriya Laras Pramesthi; Sari Kusuma; Arienta R P Sudibya; Rahmawati Rahmawati; Dini Suciyanti; Gusnedi Gusnedi; Aly Diana (PLoS ONE)
Background In Indonesia, food security and dietary patterns varied by regions. This might lead to differences in problem nutrients (PN) and should be considered in developing local-specific food-based recommendations (FBRs) for stunting prevention. Objectives This study aims to identify PNs in diet of under-five children in selected 37 stunting priority districts in Indonesia and assess whether the number of PNs was associated with district food security status. Methods Linear programming analysis (LP) using Optifood was done using single 24-hour dietary recall data Ministry of Health 2016 Food Consumption Survey. PN was defined as nutrient which did not meet 100% Recommended Nutrient Intake (RNI) based on Indonesian-RNI in the 2-best-diets scenario. District's food security status was determined using Food Security Vulnerability Atlas 2018. Results The top three PNs amongst under-five childrenwere iron, folate, vitamin B12 (6-11mo); folate, calcium, zinc (12-23mo); folate, calcium, vitamin C (24-35mo); and calcium, folate, vitamin C (36-59mo). There were no significant differences in number of PNs based on food security status. After integrating the nutrient-dense foods into FBRs, the number of districts with dietary inadequacy decreased for the top-3 problem nutrients in each age group, with the exception of iron for infants. Conclusions Our findings showed that problem nutrients and dietary inadequacy were prevalent in diet of under-five children, even in food-secure areas. Promoting locally available nutrient-dense foods through FBRs (nutrition-specific intervention) and ensuring availability and access to these foods (nutrition-sensitive intervention) are recommended. Additional intervention(s), particularly for iron in infants, are required.